Pre-clinical investigation of liquid sirolimus for local drug delivery - Todd, Meagan; Liu, Linda B.; Saul, Justin M.; Yazdani, Saami K. (Frontiers in Cardiovascular Medicine, 2023)
Sirolimus is currently being explored as an alternative drug to paclitaxel for the treatment of peripheral artery disease (PAD). To date, sirolimus has only been used as drug coatings for stents and balloons and no studies have yet demonstrated the delivery of sirolimus in liquid form. The purpose of this pilot study was to investigate the feasibility of the delivery of liquid sirolimus into arterial segments in a benchtop peripheral artery bioreactor.The feasibility to deliver liquid therapy was first tested on four drug delivery devices using a fluorescently tagged liquid drug and an ex vivo porcine artery benchtop model. The four devices included the Bullfrog Micro-infusion Device, ClearWay RX Catheter, Occlusion Perfusion Catheter (OPC), and the Targeted Adjustable Pharmaceutical Administration System (TAPAS). Penetration of the fluorescently tagged drug was measured via microscopic imaging and quantification of the depth of drug penetration into all device-treated tissue. Based on the penetration outcome, we then selected a single device to deliver liquid sirolimus into the ex vivo porcine artery model undergoing physiological flow and pressure conditions. The liquid sirolimus-treated arteries were collected from the ex vivo bioreactor at 1-hour and 24-hours post-delivery and arterial drug retention analyzed by liquid chromatography-tandem mass spectrometry.Results: Fluorescent microscopy demonstrated that drug delivery with the OPC had greater drug penetration into the medial wall as compared to other devices (OPC: 234 ± 161 µm; TAPAS: 127 ± 68 µm; ClearWay: 118 ± 77 µm; Bullfrog: 2.12 ± 3.78 µm; p<0.001). The results of the ex vivo flow-circuit bench top model showed that the OPC device successfully delivered the liquid sirolimus at 1-hour (5.14 ± 4.48 ng/mg) and 24-hours (0.78 ± 0.55 ng/mg).These results demonstrate for the first time the ability to deliver liquid sirolimus directly to the medial layer of an artery via a liquid delivery catheter.